Entrepreneurship education for climate action: the role of universities in developing NetZero startups - Yaqzan, Syed; Singh, Manish; Ihasz, Orsolya; Hussels, Stephanie; Azmat, Muhammad (Emerald, 2026)
Purpose: As climate imperatives escalate, higher education institutions are expected to mobilise entrepreneurship education for Sustainable Development Goal (SDG) delivery. This study aims to examine how entrepreneurship education shapes graduates’ creation of NetZero-oriented ventures and explains the institutional conditions that enable or inhibit this pathway. Design/methodology/approach: Using an interpretivist qualitative design, study conducted 32 semi-structured interviews with graduates (undergraduate n = 14; postgraduate n = 18) from four UK universities (graduation 2020–2023) engaged in NetZero ventures. Data was analysed using the Gioia method; demographic identifiers were used to contextualise quotations. Findings: Five cross-institutional challenges constrain the translation of sustainability awareness into entrepreneurial action: (1) limited embedding of NetZero content in core curricula; (2) inconsistent sustainability terminology; (3) insufficient implementation guidance and venture-building support; (4) over-reliance on classroom-based instruction relative to experiential learning; and (5) fragmented, weakly coordinated support across units. This study explains how these patterns arise from curriculum design choices, capability gaps in NetZero pedagogy and siloed governance that dissipate resources. Research limitations/implications: The qualitative, UK-based sample limits generalisability; future research should test these mechanisms in other contexts using mixed methods and multi-stakeholder data. Practical implications: Recommendations include embedding NetZero across entrepreneurship teaching, establishing shared terminology, providing tailored implementation support (incubation/mentoring), extending experiential learning and coordinating cross-unit ecosystems aligned with policy partners. Social implications: Stronger university ecosystems can accelerate graduate-led NetZero innovation, advancing SDGs 4 and 13. Originality/value: To the best of the authors’ knowledge, this study offers one of the first empirically grounded accounts linking entrepreneurship education to NetZero venture creation, integrating institutional and graduate perspectives.
Keywords: NetZero entrepreneurship; Sustainability in higher education; Entrepreneurship; Education; Climate action; University-based innovation; Sustainable future; 3903 Education Systems; 4 Quality Education; 17 Partnerships for the Goals; Environmental Sciences